Digital Pivot Strategies for MSMEs: A Case Study of BirkinPet in the Era of Economic Uncertainty - Zafriana, Lusi; Prihono; Nasution, Anita Hakim (Tibuana, 2025)
Amid economic uncertainty, adopting digital pivot strategies has become crucial, particularly for Micro, Small, and Medium Enterprises (MSMEs) to sustain business growth. Social media marketing, as a vital component of the digital pivot, offers a platform for entrepreneurs to reach audiences more efficiently and effectively. This study aims to explore the correlation between social media metrics and the monthly revenue of MSMEs, focusing on BirkinPet, a pet harness apparel business. A multiple linear regression analysis method was employed to evaluate the relationship between the number of posts, likes, followers, shares, and engagement rate with monthly revenue. The analysis results indicate that the number of posts has a significant negative relationship with monthly revenue (β = -1.1224; p = 0.051), while likes, shares, followers, and engagement rate showed no significant relationship. These findings highlight the importance of a more focused and relevant content strategy in social media marketing to support business revenue growth. In conclusion, while social media holds substantial potential as a marketing tool, success is not entirely dependent on the quantity of activity. A data-driven strategic approach is a key factor in converting social media activities into revenue growth, warranting further exploration to identify the most effective optimization strategies.